Impact of emergency department‐based intensive care unit on outcomes of decompensating boarding emergency department patients - Jessica Doan; Sarah Perez; Benjamin S. Bassin; Peter England; Chiu‐Mei Chen; James A. Cranford; Adam L. Gottula; Sarah Hartley; Nathan L. Haas (Journal of the American College of Emergency Physicians Open)
Abstract Objectives Emergency department (ED) boarding, or remaining in the ED after admission before transfer to an inpatient bed, is prevalent. Boarding patients may decompensate before inpatient transfer, necessitating escalation to the intensive care unit (ICU). We evaluated the impact of an ED‐ICU on decompensating boarding ED patients. Methods This is a retrospective single‐center observational study. We identified decompensated boarding ED patients necessitating critical care before departure from the ED from October 2012 to December 2021. An automated query and manual chart review extracted data. Three cohorts were defined: pre‐ED‐ICU implementation (Group 1), post‐ED‐ICU implementation with ED‐ICU care (Group 2), and post‐ED‐ICU implementation with inpatient ICU admission without ED‐ICU care (Group 3). Primary outcome was ICU length of stay (LOS). Secondary outcomes included hospital LOS, in‐hospital mortality, and ICU admissions with ICU LOS <24 hours. Between‐groups comparisons used multiple regression analysis for continuous variables, χ2 tests and multivariable logistic regression analysis for binary variables, and follow‐up contrasts for statistically significant omnibus tests. Results A total of 1123 visits met inclusion criteria: 225 in Group 1, 780 in Group 2, and 118 in Group 3. Mean ICU LOS was shorter for Group 2 than Group 1 or 3 (47.4 vs 92.3 vs 103.9 hours, P < 0.001). Mean hospital LOS was shorter for Group 2 than Group 1 or 3 (185.1 vs 246.8 vs 257.3 hours, P < 0.01). In‐hospital mortality was similar between groups. The proportion of ICU LOS <24 hours was lower for Group 2 than Group 1 or 3 (16.5 vs 27.1 vs 32.2%, P < 0.01). Conclusion For decompensating boarding ED patients, ED‐ICU care was associated with decreased ICU and hospital LOS, similar mortality, and fewer short‐stay ICU admissions, suggesting ED‐ICU care is associated with downstream resource preservation.